Energy efficiency and industrial output: The case of the iron and steel industry - Florens Flues; Dirk Rübbelke; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
The iron and steel industry is one of the most carbon emitting and energy consuming sectors in Europe. At the same time this sector is of high economic importance for the European Union. Therefore, while public environmental and energy policies target this sector, there is political concern that it suffers too much from these policy measures. Various actors fear a policy-induced decline in steel production, and possibly an international reallocation of production plants. This study analyzes the role that input prices and public policies may play in attaining an environmentally more sustainable steel production and how this - in turn - affect total steel output. As we find out for examples of major European steel producing countries, a kind of rebound effect of energy-efficiency improvements in steel production on total steel output may arise.
urn:nbn:de:bsz:180-madoc-352731
Keywords: L51; L61; Q43; Q50; 330; energy efficiency; iron and steel industry; environmental protection; rebound effect